Um prefácio a povos da Guiné-Bissau: o Boletim Cultural da Guiné Portuguesa (1946-1973) - Leister, Fátima Cristina (2012)
In spite of the publication of Law 10.369 in 2003, which made the teaching of the history and culture of Africa and African Brazilians compulsory, there is still much to be done to reduce the defects in the national curriculum and offer better guidance for the study of the Africas and of Africans. There are still many avenues that need to be explored in order to fill the gaps that the colonial legacy has left. To this end, in order to broaden historical horizons and contribute to the historiographical debate already under way, the focus of the present work is directed at the area occupied by current Guinea-Bissau, especially during the period of the Imperial Colonial Portuguese Empire. This area has been almost totally neglected in Brazil, but the culture of Guinean people has been described in the annals of the Boletim Cultural da Guiné Portuguesa. This colonial periodical, published between 1946 and 1973 is now available online as the Projeto Memória de África e Oriente. Coordinated by the Fundação Portugal-Africa, the aim of this project is to collect, collate and digitalize documents at present scattered among the documentation centers of various Portuguese-speaking countries and make them available to researchers on the internet. The Boletim Cultural is a varied source made up of 110 editions published uninterruptedly three times a year. There are over 20,000 pages, whose main emphasis is on articles concerning ethnographics, which, although often seen from an undesirably European perspective, offer the opportunity to study these little-known cultures, which have been mostly handed down by oral tradition, and despite the cultural bias they display, these articles are nevertheless well worth reading. In fact, paradoxically, this alien perspective serves to highlight certain cultural features and the very characteristic language used in them expresses quite pointedly the colonial logic upon which political and scientific studies were based. In this way, this scientific knowledge, despite its subtexts, has enabled a dialog to take place with various actors who made their own history, despite this remaining restricted even until today, by others who sought to control it. Thus, despite being strongly influenced by scientific colonial attitudes, these studies published in the pages of Boletim Cultural, did allow the first approaches to be made to Guinea-Bissau and its constituent elements in the 20th century